A three-topology based, wide input range switched-capacitor DC-DC converter with low-ripple and enhanced load line regulations - Yang, Yongkui (2015)
This paper presents a novel switched-capacitor (SC) DC-DC converter that incorporates three conversion topologies. At 100 kHz, the design is proposed to cater to wide input range, of 2.5 V to 4.5 V. Excellent accuracy and output regulation capabilities are obtained with output ripple voltage and error of < 6 mV and < 1.3%, respectively, when operated with a fixed output voltage of 1 V. A proportional-integral (PI) compensator is constructed for close-loop feedback compensation where it successfully enhanced both the load and line regulations. Finally, the peak efficiency of 70.76% is obtained at full load.